(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Public health is highly dependent on the quality of drinking water. Access to safe drinking waterremains a challenge despite recent advances in the field. The World Health Organization estimates that10 of the global population does not have access to improved water quality, and one of the UnitedNations’ Sustainable Development Goals is to ensure that everyone can use a toilet 2030. Up to a millionindividuals every year lose their lives because of waterborne bacteria that cause diarrhea. They’re mostlyless than five years old. Even though it has been there for a while in the wealthy world, chemicalpollution is only growing in frequency in low- and middle-income countries. Numerous chronic diseases,such as cardiovascular disease and cancer, and adverse reproductive outcomes have been linked tochemical exposure in drinking water and negative impacts on children’s health, such asneurodevelopment.